Organoids in precision medicine: the rise of miniature tissue models in research - Maddalena Paganucci (The Biochemist, 2026)
Abstract Recent advances in biomedical research have increased demand for experimental systems capable of capturing human biological processes with greater physiological relevance than traditional approaches. However, direct investigation of cellular dynamics remains constrained by the invasive nature of many methodologies, the limited viability of human tissue samples, and the translational shortcomings of animal models. Organoid technology has emerged as a powerful alternative, enabling the generation of three-dimensional tissue-like structures from pluripotent or adult stem cells that reproduce key structural and functional characteristics of native organs. Through self-organisation and preservation of donor-specific genetic information, organoids provide physiologically representative platforms for studying disease mechanisms, host–pathogen interactions, therapeutic responses, and interindividual variation. The present narrative review outlines the scientific foundations underpinning organoid development, tracing their emergence from advances in tissue engineering and three-dimensional culture systems. The limitations of conventional in vitro and in vivo models are examined alongside the advantages offered by organoid platforms for long-term investigation of human physiology and pathology. Particular emphasis is placed on their growing role in precision medicine, including disease modelling, drug discovery, toxicity assessment, and patient stratification. Emerging applications in regenerative medicine and transplantation are also discussed, together with current technical challenges such as vascularisation and tissue integration. Collectively, organoid systems represent a transformative tool for biomedical research, offering new opportunities to improve and personalise therapeutic strategies, ultimately advancing translational medicine.